Assessment of data‐limited fisheries: A case study of three finfish species in Chilika lagoon, India. (20th December 2022) - Suresh, Vettath Raghavan; Varghese, Eldho; Sajina, Aliyamintakath M.; Karna, Subodha Kumar; Mohanty, Surya K.; Sethi, Pradeep K.; Mukherjee, Manasi; Banik, Surajit K.; Jayaraman, Jayasankar; Munivenkatappa, Manas H.; Mukherjee, Jayanta; Manna, Ranjan K.; et al.
Abstract: Inland capture fisheries in many parts of the world, especially in developing nations, receive relatively low governance priority, thereby raising concerns about their sustainability. Consequently, most inland capture fisheries are data‐limited, which renders conventional capture fisheries assessment methods inapplicable for making science‐based monitoring and management decisions. Three recent data‐limited approaches for marine fish stock assessments using length frequency and catch data (Length‐Based Indicators [LBI], Growth‐Type Groups Length‐Based Spawning Potential Ratio [GTG‐LBSPR] and Catch Maximum Sustainable Yield [CMSY]), were explored for applicability to assess stock status of three commercially exploited finfish species, Daysciaena albida, Eleutheronema tetradactylum and Mugil cephalus, in Chilika lagoon, an inland water body along the east coast of India. The LBI and GTG‐LBSPR approaches are based on catch length‐frequency data, while the CMSY is based on catch‐only data. The LBI provided insight into current exploitation status of the three species in relation to sustainable fishing, the GTG‐LBSPR provided reference points (RP) for the unfished portion of spawning biomass and relative yield in relation to selectivity, and the CMSY provided RPs for MSY, biomass and fishing pressure that yield MSY, to assess stock status and fishery management decisions. All three approaches suggested that the three species were overfished in terms of catch length and quantity, which agreed with expert knowledge of the fishery in the lagoon. All three approaches can support management and policy decisions in inland fisheries and fishery management recommendations. Future research should explore and standardise such approaches to overcome data limitations in assessing and managing inland capture fisheries.